Gravitational Erythema: Case Study and Differential Diagnosis - Nina T. Garipova; Mariam M. Gharabaghtsyan; Lubov S. Sorokina; Mikhail M. Kostik (Вопросы современной педиатрии)
Background. Gravitational erythema is rare pathologic condition that is characterized by abnormal vascular response on venous pressure changes. It is benign disease, and it is included in differential diagnosis of vasculitis, vasculopathies, neuropathies and does not require treatment. Compression garments may be required in some cases.Clinical Case Description. The case of gravitational erythema in 13 years old patient of is presented. The disease was presented with erythematous mosaic rash on the lower limbs skin. It has appeared in 4-6 minutes after verticalisation and mostly on the lower legs. The rash was accompanied with some bluish spots disappearing after pressure. The elements of rush were itchy, there was pain in distal parts of the feet. The rash was reversed after walking and changing of limb position. Positive compression test was mentioned.Conclusion. Differential diagnosis of gravitational erythema with other clinically similar conditions remains relevant. The rare diagnosis of gravitational erythema and low awareness of doctors about it cause misdiagnosis, costly continuous examination and ineffective treatment.